Cancel culture: Exploring the unintended consequences of cancelling the Canadian national licensing clinical examination - Touchie, Claire; Pugh, Debra (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Assessment drives learning. However, when it comes to high-stakes examinations (e.g., for licensure or certification), these assessments of learning may be seen as unnecessary hurdles by some. Licensing clinical skills assessment in particular have come under fire over the years. Recently, assessments such as the Medical Council of Canada Qualifying Examination Part II, a clinical skills objective structured clinical examination, have been permanently cancelled. The authors explore potential consequences of this cancellation including those that are inadvertent and undesirable. Future next steps for clinical skills assessment are explored.